Pengolahan Zat Warna Tekstil (Rhodamine B) Dengan Teknologi AOP (Advance Oxidation Processes) Menggunakan Katalis Ce@Carbon Sphere Dan Oksidan Peroxymonosulfate - Ilok Dianggoni; Edy Saputra; Jhon Armedi Pinem (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Waste water of textile industry contributes in environmental pollution, especially wastewater containing dye and organic compounds are dangerous because they are non-biodegradable, toxic and harmful to the environment, like as Rhodamine B. Therefore, it is necessary to do the processing of waste dye textile industry to reduce the impact of pollution on the environment. One of the lastest innovations in the processing of textile waste is using advanced oxidation processes (AOPs) by oxidant capable of generating a radical sulphate (SO4*). This study aims to determine the activity of Ce@Carbon Sphere as a catalyst in the oxidation process, to degradation of dye in wastewater by using a combination of peroxymonosulfate and catalyst Ce@Carbon Sphere as an oxidater, and determine the optimum conditions to reduce dye in water. Catalytic synthesis process carried out by the hydrothermal process to produce black carbon from D-glucose and Cerium Nitrate Hexahidrate solution, at 180oC for 18 hours in an autoclave. Then calcined with N2 at 550oC for 2 hours. Degradation of Rhodamine B (waste artificially) 25 ppm for 2 hours with various concentrations of the catalyst 0,1; 0,2; 0,3 and 0,4gr/L and the concentration proxymonosulfate 1; 2; 3 and 4 g/L. One oft the conditions for reducing the levels of Rhodamine B in water is concentration of peroxymonosulfate at 1 g/L and Ce@Carbon Sphere at 0,1 g/L with efficiency up to 32,59%.Keywords: AOPs, Rhodamine B, Ce@Carbon Sphere, Peroxymonosulfate